Explaining Murder in Maine: Three Case Studies. Issue 6 (3rd June 2018) - Riley, John
ABSTRACT: Research suggests that popular depictions of crime and criminals are influenced by a dominant ideology that explains crime in terms of the individual failings of criminals, while ignoring social contributions to crime rates. The research reported here, based on an ethnographic content analysis of newspaper depictions of 108 murderers, identifies and describes three case studies of criminal homicide which challenge the dominant ideology by highlighting social contributions to crime. These cases suggest that an alternative ideology which explains crime with reference to institutional processes and collective responsibility may be identified in newspaper accounts of murder in Maine.